2003
DOI: 10.1034/j.1600-0447.108.s418.4.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the bipolar and depression spectra

Abstract: Objective:  To identify risk factors for mood disorders in a community sample studied from the ages of 20 to 35 years. Method:  Social characteristics, a family history of mood disorders and some personality features were analysed as risk factors for bipolar and depressive disorders by means of logistic regression. Results:  Frequent ‘ups and downs’ of mood were the strongest risk factor for both bipolar and depressive disorders; a weaker risk factor for both was emotional/vegetative lability (neuroticism). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 11 publications
(9 reference statements)
1
109
0
1
Order By: Relevance
“…This was simple to understand and appropriate given its use in over 7000 people and consistent with other previous mood instability research [44]. A very similar mood instability question, as the one used in the current analysis has been utilised in other epidemiological research and responses found to predict future diagnosis of bipolar disorder [45]. One method increasingly advocated as a way to measure mood instability is ecological momentary assessment [3], but the demand that it places on respondents makes its use in household surveys a challenge.…”
Section: Discussionmentioning
confidence: 66%
“…This was simple to understand and appropriate given its use in over 7000 people and consistent with other previous mood instability research [44]. A very similar mood instability question, as the one used in the current analysis has been utilised in other epidemiological research and responses found to predict future diagnosis of bipolar disorder [45]. One method increasingly advocated as a way to measure mood instability is ecological momentary assessment [3], but the demand that it places on respondents makes its use in household surveys a challenge.…”
Section: Discussionmentioning
confidence: 66%
“…Abnormalities in these tracts have been found in studies of unipolar depression Cullen et al 2010 ;Dalby et al 2010) and people at high familial risk of major mental illness . There is also a growing body of literature showing abnormal frontotemporal activation and connectivity in depression (Anand et al 2005a,b) and in a variety of other mental disorders (Lawrie et al 2002 ;Chepenik et al 2010) for which neuroticism is an identified risk factor (Maier et al 1994 ;van Os & Jones, 2001 ;Angst et al 2003 ;Barnett et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This burgeoning interest is for several reasons. First, AI appears to be a prognostic marker for transition status in those at risk of bipolar disorder (Angst et al, 2003;Howes et al, 2011). Secondly, automated, persistent time series measurement of mood, analysed using advanced mathematical techniques has revealed a complex pattern of AI in the euthymic periods of people with bipolar disorder (Bonsall et al, 2012) reflecting an abnormality in affective reactivity .…”
Section: Introductionmentioning
confidence: 99%